Hubungan Peran Orang Tua dengan Risiko Penularan (Status Imunisasi, Status Gizi, dan Perilaku) Difteri pada Balita di Desa Paowan Kecamatan Panarukan Kabupaten Situbondo (Correlation Between the Role of Parents and Risk of Diphtheria Transmission (Imuniza - Triaji Windiarta Sundoko; Hanny Rasni; Ratna Sari Hardiani (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Diphtheria is transmission disease and dangerous for human living. Death usually happened on third to fourth day from the first day disease appearing. Mortality of diphtheria in Situbondo has higher number than other city. Preventions of diphtheria are immunization, increase of nutrient state, and improvement of parent behavior for decreasing the death of this disease. This research was intended to analyse Correlation of role of parents and risk of transmission (immunization status, nutrient status, and behavior) diphtheria in children under five in Paowan Village of Panarukan Subdistrict at Situbondo Regency. This research applied observational analytic method with crosssectional approach. Sampling technique used random sampling and the sample consisted of 61 respondens. Data analysis used chi-square and the result showed that the p-value 0,003 (p-value